The Viro Method for Construction of Piecewise Algebraic Hypersurfaces - Yisheng Lai; Weiping Du; Renhong Wang (Abstract and Applied Analysis)
We propose a new method to construct a real piecewise algebraic hypersurface of a given degree with a prescribed smoothness and topology. The method is based on the smooth blending theory and the Viro method for construction of Bernstein-Bézier algebraic hypersurface piece on a simplex.